The Genetic Basis of Scale-Loss Phenotype in the Rapid Radiation of Takifugu Fishes - Kim, Dong In (Genes (Basel), 2019)
Rapid radiation associated with phenotypic divergence and convergence provides an opportunity to study the genetic mechanisms of evolution. Here we investigate the genus Takifugu that has undergone explosive radiation relatively recently and contains a subset of closely-related species with a scale-loss phenotype. By using observations during development and genetic mapping approaches, we show that the scale-loss phenotype of two Takifugu species, T. pardalis Temminck & Schlegel and T. snyderi Abe, is largely controlled by an overlapping genomic segment (QTL). A search for candidate genes underlying the scale-loss phenotype revealed that the QTL region contains no known genes responsible for the evolution of scale-loss phenotype in other fishes. These results suggest that the genes used for the scale-loss phenotypes in the two Takifugu are likely the same, but the genes used for the similar phenotype in Takifugu and distantly related fishes are not the same. Meanwhile, Fgfrl1, a gene predicted to function in a pathway known to regulate bone/scale development was identified in the QTL region. Since Fgfr1a1, another memebr of the Fgf signaling pathway, has been implicated in scale loss/scale shape in fish distantly related to Takifugu, our results suggest that the convergence of the scale-loss phenotype may be constrained by signaling modules with conserved roles in scale development.